Vertical Integration of Hospitals and Physicians: Economic Theory and Empirical Evidence on Spending and Quality. (August 2018) - Post, Brady; Buchmueller, Tom; Ryan, Andrew M.
Hospital–physician vertical integration is on the rise. While increased efficiencies may be possible, emerging research raises concerns about anticompetitive behavior, spending increases, and uncertain effects on quality. In this review, we bring together several of the key theories of vertical integration that exist in the neoclassical and institutional economics literatures and apply these theories to the hospital–physician relationship. We also conduct a literature review of the effects of vertical integration on prices, spending, and quality in the growing body of evidence ( n = 15) to evaluate which of these frameworks have the strongest empirical support. We find some support for vertical foreclosure as a framework for explaining the observed results. We suggest a conceptual model and identify directions for future research. Based on our analysis, we conclude that vertical integration poses a threat to the affordability of health services and merits special attention from policymakers and antitrust authorities.